The application of resistivity and EM method to monitor vinasse infiltration in sandy sediments - Malagutti Filho, W. [UNESP]; Bortolin, J. R M [UNESP]; Moreira, C. A. [UNESP]; Pereira, A. M. [UNESP] (My University, 2014)
The cultivation of sugar cane represents one of the most important agricultural supplies in Brazil. One one of its driving factors is the production of etanol, a widely used fuel for Brazilian automobiles. Among the residue related to the production of etanol, the vinasse is highlighted, a liquid substance generated in the ratio of approximately 13 liters to each liter of etanol that is produced. This paper proposes to identify the geophysical signature related to controlled vinasse infiltration in sandy sediments, as well as to monitor the contaminated plume through the use of investigational electrical resistivity and electromagnetic geophysical methods. The study was performed on a 100m2 (10m x 10m) rural area near the municipality of Corumbataí, inland Sao Paulo State, Brazil, in sandy sediments from Pirambóia Formation. Two trenches of approximately 0,45m x 0,45m x 2,00 (total approximate volume of 405 liters) were excavated in the area to receive the vinasse infiltration. The electrical measurements were carried out in two separate rounds: before and after excavating the trenches and infiltrating the vinnase. The observed anomalies presented low resistivity in the ER method and the anomalies shown by the EM method, they can be conductive or resistive, depending on the investigated depth.